2013
DOI: 10.1038/cmi.2012.77
|View full text |Cite
|
Sign up to set email alerts
|

NOD-like receptors mediated activation of eosinophils interacting with bronchial epithelial cells: a link between innate immunity and allergic asthma

Abstract: Key intracytosolic pattern recognition receptors of innate immunity against bacterial infections are nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs). We elucidated the NOD1 and NOD2-mediated activation of human eosinophils, the principal effector cells for allergic inflammation, upon interacting with human bronchial epithelial BEAS-2B cells in allergic asthma. Eosinophils constitutively expressed NOD1,2 but exhibited nonsignificant responses to release chemokines upon the stimulation by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…NOD2 and TLR2 are the pivotal PRRs responsible for the immune recognition of S. aureus and are prevalently expressed on innate immune cells, including basophils and eosinophils. [20][21][22][23] Moreover, our results provide the first evidence showing that IL-3C-expanded basophils and eosinophils further deteriorate AD-like inflammation in mice treated with epicutaneous S. aureus components and that the targeted experimental depletion of these innate immune cells protects mice from IL-3C-exacerbated skin inflammation (Figure 2 and Supplementary Figure S4). …”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…NOD2 and TLR2 are the pivotal PRRs responsible for the immune recognition of S. aureus and are prevalently expressed on innate immune cells, including basophils and eosinophils. [20][21][22][23] Moreover, our results provide the first evidence showing that IL-3C-expanded basophils and eosinophils further deteriorate AD-like inflammation in mice treated with epicutaneous S. aureus components and that the targeted experimental depletion of these innate immune cells protects mice from IL-3C-exacerbated skin inflammation (Figure 2 and Supplementary Figure S4). …”
Section: Discussionmentioning
confidence: 66%
“…22,23 In the present study, both the p38 MAPK and NFkB pathways were found to be essential for the NOD2/TLR2 ligand-mediated activation of basophils and eosinophils by interacting with dermal fibroblasts. However, the ERK pathway was indispensable for the activation of eosinophils (but not basophils) co-cultured with dermal fibroblasts (Figure 7).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations